Low-carbon ore grinding process for improving yield of particle fraction of-325 +400 meshes
By using mixed grinding medium of nanocomposite ceramic balls and steel balls in grinding technology, the problems of insufficient fine grinding and poor grinding graded effects in the existing technology are solved, and efficient iron concentrate production is achieved, which has improved the Product taste and resource utilization.
Patent Information
- Application Number
- CN202411878772.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-14
AI Technical Summary
The existing grinding technology is difficult to achieve a fine grinding degree of -0.045mm accounting for more than 90% while ensuring plant production capacity, resulting in less than 64% of iron concentrate grade, and the grinding grade effect of the third-stage tower mill is poor. , overgrinding occurs.
Using nanocomposite ceramic balls as the main grinding medium and paired with steel balls with a certain volume proportion, the best ratio of porcelain balls to steel balls is determined through screening experiments and tests of multiple proportioning conditions to improve grinding products The content of -0.045mm is improved, and the grinding efficiency and concentrate grade of the tower mill are improved.
Significantly improves the -0.075mm yield and qualified particle grade yield of grinding products, reduces the yield of under-aggrinding particles, improves the grade and recovery rate of iron concentrate, reduces energy consumption, and improves the comprehensive benefits of ore dressing plants. .
Smart Images

Figure CN119425898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ore grinding, in particular to a low-carbon ore grinding process for improving the yield of -325+400 mesh particle size. Background Art
[0002] Grinding is the continuation of the crushing process. In order to separate the gangue minerals in the ore and separate various useful minerals from each other, it is necessary to separate the various minerals into monomers first. It is difficult to achieve the monomer separation of minerals by crushing alone. Because the impregnation of minerals is often not uniform, mineral particles with a particle size of several millimeters and particles with a particle size of several microns (several thousandths of a millimeter) exist. Therefore, in order to achieve the monomer separation of minerals, the ore is ground to the particle size required for the separation operation by the method of grinding. Therefore, the grinding operation is one of the more critical operations in the production of the ore dressing plant. The ore of a certain beneficiation plant is a very poor magnetite ore with fine grains embedded in it. It needs fine grinding and deep selection to obtain high-grade iron concentrate. According to the analysis of the ore dressing test, if this type of ore is to ensure the iron concentrate grade of 65% in industrial production, it needs to be finely ground to -0.045mm, accounting for more than 90%.
[0003] However, under the premise of ensuring the production capacity of the concentrator, the existing grinding fineness can only reach -0.075mm, accounting for 95% (-0.045mm, accounting for about 85%), and the grade of iron ore concentrate is less than 64%. The feed fineness of the three-stage tower mill (-0.075mm) is 62.25%. Among them, the yield of the newly generated -0.045+0.038mm is only about 6%, and over-grinding occurs, which is far below the normal production requirements on site. The above shows that the three-stage grinding and classification effect is poor, which is not conducive to stable production. Therefore, it is necessary to improve the grinding and classification effect by redesigning the porcelain ball filling and replenishing ball process. Summary of the invention
[0004] The purpose of the present invention is to provide a low-carbon grinding process for improving the yield of -325+400 mesh particle size. By replacing the grinding medium steel balls with nano-composite ceramic balls and then matching them with steel balls with a certain volume ratio, the -0.045mm content of the grinding product can be increased, the grinding efficiency, concentrate grade and recovery rate of the tower mill can be improved, energy saving and consumption reduction can be achieved, and the comprehensive benefits of the ore dressing plant can be improved, thereby solving the problems raised in the above-mentioned background technology.
[0005] To achieve the above object, the present invention provides the following technical solutions:
[0006] A low-carbon grinding process for improving the yield of -325+400 mesh size, comprising:
[0007] S1. Perform a screening experiment on the material fed into the tower mill to obtain a feed particle size composition table;
[0008] S2. Combined with the feed particle size composition table, two diameters of steel balls were selected for benchmark experiments, with a ratio of 1:1, a filling rate of 40%, and a grinding concentration of 65%, to obtain the optimal grinding time;
[0009] S3. To explore the effect of different diameters of ceramic balls on the particle size distribution of grinding products, grinding was carried out under the conditions of filling rate of 60% and grinding concentration of 65% with single ceramic ball sizes of Φ15mm, Φ20mm, Φ25mm and Φ30mm respectively;
[0010] S4, combining the single porcelain ball size experimental results in S3, conducting experiments on various porcelain ball diameter ratio conditions to determine an optimal porcelain ball diameter ratio scheme;
[0011] S5. Determine the initial ball loading system of the porcelain balls, determine the optimum filling rate of the porcelain balls, and on this basis select different concentrations to conduct grinding concentration tests to obtain the optimum grinding concentration;
[0012] S6. Add steel balls appropriately to the determined porcelain ball ratio to reduce the under-abrasive grade, and select the most suitable size of steel balls as the steel ball + porcelain ball mixed grinding medium by repeating the operation of S3;
[0013] S7. Determine the steel ball + ceramic ball mixed grinding scheme, select several steel ball volume ratio schemes, and compare the experimental results with all-ceramic ball grinding. By adding steel balls to the optimal ceramic ball ratio, the -0.075mm yield and qualified particle size yield in the grinding product are increased, and the under-grinding particle size yield is reduced.
[0014] S8. Determine the conditions for the mixed grinding of steel balls and porcelain balls in the tower mill, grind at total filling rates of 55%, 60%, and 65%, select the best filling rate for the tower mill grinding experiment, and determine the final grinding plan.
[0015] Preferably, with respect to S2, steel balls with diameters of Φ20 mm and Φ15 mm are selected as benchmark experiments to determine that the optimal grinding time is 5 minutes.
[0016] Preferably, with respect to S4, a Φ20 mm porcelain ball is selected as the optimal size, and the best porcelain ball diameter ratio is determined to be Φ25 mm:Φ20 mm:Φ15 mm=60%:20%:20%.
[0017] Preferably, as described in S5, during the filling rate experiment, as the filling rate of the porcelain balls increases, the -0.075mm yield in the grinding product gradually increases. When the filling rate reaches 60%, the -0.075mm yield is 78.51%, the under-abrasive grade yield is 9.03%, and the -0.045+0.038mm yield is 24.77%, and the grinding effect is optimal.
[0018] Preferably, as described in S6, when 25 mm steel balls are used as grinding media, the yield of the new-0.075 mm diameter steel balls is higher than that of steel balls of other diameters, and the yield of the under-abrasive grade is the lowest.
[0019] Preferably, as described in S7, after adding steel balls, the -0.075mm yield and qualified particle size yield in the ground product are increased, and the under-abrasive grade yield is reduced. Among them, when the volume of the steel balls accounts for 4%, the -0.075mm yield of the ground product is the highest, which is 87.33%, and the under-abrasive grade content is the lowest, which is 6.95%.
[0020] Preferably, the process is suitable for a tower mill model of TGTM-1000 with an effective cylinder volume of 49m 3 Among them, the total amount of initially installed porcelain balls is about 60 tons, the total amount of initially installed steel balls is about 7 tons, and 3 tons of steel balls are reserved for additional additions depending on production conditions. Φ25mm porcelain balls and Φ20mm steel balls are added on a daily basis.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention adopts nano-composite ceramic balls as the main grinding medium. Under the same specifications, the crushing energy of nano-composite ceramic balls is more than 50% lower than that of steel balls. The over-abrasive particle size (-0.019mm) produced by ceramic balls during grinding is much lower than that of steel balls. Compared with traditional steel balls, it has lower crushing energy requirements and reduces over-grinding.
[0023] 2. The present invention determines the best ratio of porcelain balls to steel balls through experiments, which not only improves the yield of -325+400 mesh size, but also reduces the under-grinded size. The optimum grinding concentration is determined to be 67%, and the total filling rate is 60%. The fineness of the ground product and the yield of the qualified size are both optimal. At the same time, the over-grinding problem caused by the excessively high filling rate is avoided, and the product quality and resource utilization rate are effectively improved.
[0024] 2. In the present invention, the filling rate of nano-composite ceramic balls in the tower mill is higher than that of steel balls, and the size used is smaller. The overall ceramic ball grinding medium has a larger specific surface area, and its fine-grained grinding ability is stronger than that of steel balls. The ceramic ball also has better anti-wavelength ability than steel balls.
[0025] 3. In the present invention, the porcelain balls have good wear resistance, the mill has low noise during operation, and the slurry temperature is low, which can greatly reduce the loss of grinding energy in the form of sound energy and heat energy, which is beneficial to improving energy utilization efficiency and achieving energy saving and consumption reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the process flow of the present invention;
[0027] Figure 2The figure is the particle size composition and metal content distribution of the tower mill feed of the present invention (%);
[0028] Figure 3 It is a comparison chart (%) of magnetic separation indexes of porcelain ball grinding and steel ball grinding products of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] In order to solve the problem that the existing tower mill using steel balls as the medium often has the phenomenon of over-grinding, in which the newly generated -0.045+0.038mm has low yield and a large number of under-grinded particles, this embodiment provides the following technical solutions:
[0031] A low-carbon grinding process for improving the yield of -325+400 mesh size, comprising:
[0032] S1. Perform a screening experiment on the material fed into the tower mill to obtain a feed particle size composition table;
[0033] S2. Combined with the feed particle size composition table, two diameters of steel balls were selected for benchmark experiments, with a ratio of 1:1, a filling rate of 40%, and a grinding concentration of 65%, to obtain the optimal grinding time;
[0034] S3. To explore the effect of different diameters of ceramic balls on the particle size distribution of grinding products, grinding was carried out under the conditions of filling rate of 60% and grinding concentration of 65% with single ceramic ball sizes of Φ15mm, Φ20mm, Φ25mm and Φ30mm respectively;
[0035] S4, combining the single porcelain ball size experimental results in S3, conducting experiments on various porcelain ball diameter ratio conditions to determine an optimal porcelain ball diameter ratio scheme;
[0036] S5. Determine the initial ball loading system of the porcelain balls, determine the optimum filling rate of the porcelain balls, and on this basis select different concentrations to conduct grinding concentration tests to obtain the optimum grinding concentration;
[0037] S6. Add steel balls appropriately to the determined porcelain ball ratio to reduce the under-abrasive grade, and select the most suitable size of steel balls as the steel ball + porcelain ball mixed grinding medium by repeating the operation of S3;
[0038] S7. Determine the steel ball + ceramic ball mixed grinding scheme, select several steel ball volume ratio schemes, and compare the experimental results with all-ceramic ball grinding. By adding steel balls to the optimal ceramic ball ratio, the -0.075mm yield and qualified particle size yield in the grinding product are increased, and the under-grinding particle size yield is reduced.
[0039] S8. Determine the conditions for the mixed grinding of steel balls and porcelain balls in the tower mill, grind at total filling rates of 55%, 60%, and 65%, select the best filling rate for the tower mill grinding experiment, and determine the final grinding plan.
[0040] like Figure 1 As shown in FIG. 1 , the material fed into the tower mill (cyclone sand settling) was first subjected to a screening experiment. The experiments used 0.3 mm (50 mesh), 0.15 mm (100 mesh), 0.075 mm (200 mesh), 0.045 mm (325 mesh), 0.038 mm (400 mesh) and 0.030 mm (500 mesh) sieves to obtain the following: Figure 2 Particle size distribution and grade are shown.
[0041] The analysis of the feed particle size of the tower mill and the concentrator index show that the feed particle size in the range of -0.045+0.038 has reached the standard. The iron grade gradually increases with the particle size becoming finer, indicating that in order to obtain an iron concentrate with a grade of more than 66%, it is necessary to grind it to less than -0.045mm (325 mesh). For the fine grinding of this mineral, it is necessary to pay attention to the grinding of the under-abrasive grade and reduce the generation of the over-abrasive grade.
[0042] It is planned to use steel balls and ceramic balls with diameters of 15mm, 20mm, 25mm and 30mm as grinding media for tower mill for grinding experiments. The tower mill model is TGTM-1000, the feed rate is 85-100t / h, the spiral speed is 28r / min, and all the experiments are particle size analysis experiments. After each change of grinding conditions, a part of the grinding product is taken for drying and screening experiments.
[0043] Using steel balls with diameters of 20mm and 15mm, the ratio is Φ20mm:Φ15mm=1:1, the filling rate is 40%, the grinding concentration is 65%, and the grinding time experiments are carried out at grinding times of 3min, 4min, 5min, and 6min respectively. When the grinding time is 5min, the fineness of the grinding product (-0.075mm) is 70.85%, and the new -200 mesh is the largest, which meets the requirements of on-site grinding operations. Therefore, the grinding time of 5min is selected as the optimal grinding time for the vertical mill.
[0044] The particle size distribution of grinding products of different ball diameters was investigated, with a filling rate of 60% and a grinding concentration of 65%. Grinding was performed under single ball sizes of Φ15mm, Φ20mm, Φ25mm, and Φ30mm. The results showed that when the ball diameter was 20mm, the yield of the grinding product -0.075mm was the highest at 66.97%, while the yield of +0.15mm was the lowest at 11.74%. The results showed that the mixed ratio of ceramic balls would have a better grinding effect than the single ball diameter of ceramic balls.
[0045] Combined with the results of the single ball diameter test, the ball diameter ratio test was conducted to determine the best ball diameter ratio. 25mm, 20mm, and 15mm balls were selected as grinding media, and four representative ratios were selected:
[0046] ①Φ25mm: Φ20mm: Φ15mm=60%: 20%: 20%;
[0047] ②Φ25mm: Φ20mm: Φ15mm=40%: 40%: 20%;
[0048] ③Φ25mm: Φ20mm: Φ15mm=20%: 60%: 20%;
[0049] ④Φ25mm: Φ20mm: Φ15mm=20%: 40%: 40%.
[0050] The filling rate is 60%, the grinding concentration is 65%, and the screw speed is 28r / min.
[0051] The screening results show that the yield of -0.075mm in the ① ratio is the highest, which is 78.51%, and the yield of the new generation of -0.045+0.038mm is 14.68%, and the yield of the under-abrasive grade in the ① ratio is 9.03%, which is the lowest among the four ratios. Finally, the ① ratio was selected as the best ceramic ball diameter ratio.
[0052] Determine the initial charging system of porcelain balls as Φ25mm:Φ20mm:Φ15mm=60%:20%:20%; spiral speed is 28r / min, grinding concentration is 65%; select filling rates of 58%, 60%, 62%, and 64% for filling rate experiments. As the filling rate of porcelain balls increases, the probability of porcelain ball collision increases, and the yield of -0.075mm in the grinding product gradually increases. When the filling rate reaches 60%, the yield of -0.075mm is 78.51%, the yield of under-abrasive grade is 9.03%, and the yield of -0.045+0.038mm is 24.77%, and the grinding effect is best.
[0053] The filling rate is 60%, the porcelain ball filling system is Φ25mm:Φ20mm:Φ15mm=60%:20%:20%, and the spiral speed is 28r / min; grinding concentrations of 60%, 64%, 67% and 70% were selected for grinding concentration tests. The particle size distribution of the grinding products showed that when the grinding concentration was 67%, the -0.075mm yield of the porcelain ball grinding product was the highest at 86.75%, while the -0.045+0.038mm yield was the highest at 28.79%, and the under-grinding grade yield was the lowest at 7.56%. The product particle size distribution was relatively uniform.
[0054] In order to reduce the under-abrasive grade, steel balls are appropriately added to the determined porcelain ball ratio. In order to determine the diameter of the additional steel balls, the porcelain balls are replaced with steel balls and S3 is repeated. The experimental results show that when 25mm steel balls are used as grinding media, the yield of new-0.075mm is higher than that of steel balls with other diameters, and the yield of the under-abrasive grade is the lowest. Therefore, 25mm steel balls are selected as the steel ball + porcelain ball mixed grinding media.
[0055] Determine the steel ball + porcelain ball mixed grinding scheme. Specifically, the ratio scheme is: steel ball Φ25 + porcelain ball Φ25:20:15=6:2:2, divided into three groups:
[0056] ①The volume of steel balls accounts for 2%;
[0057] ②The volume of steel balls accounts for 4%;
[0058] ③The volume of steel balls accounts for 6%;
[0059] The experimental results were compared with those of all-ceramic ball grinding. By adding steel balls to the optimal ceramic ball ratio, the -0.075 mm yield and qualified particle size yield in the grinding product increased, and the under-grinding particle size yield decreased.
[0060] Among them, the grinding product of the ② ratio -0.075mm has the highest yield, which is 87.33%, and the grinding effect is the best. At the same time, the content of under-abrasive particles is the lowest at 6.95%, and the yield of -0.045+0.038mm is also higher than the other two groups. Therefore, steel ball + ceramic ball ② is selected as the best ratio, and the volume of 25mm steel ball accounts for 4%.
[0061] Determine the experimental grinding conditions of tower mill steel ball + porcelain ball mixed grinding: feed rate 85-100t / h, grinding concentration 67%, porcelain ball loading system Φ25mm:Φ20mm:Φ15mm=60%:20%:20%, steel balls with a ball diameter of Φ25mm account for 4% of the volume, and grinding is carried out under the conditions of total filling rates of 55%, 60% and 65% respectively. Through the experimental screening results, it can be found that when the filling rate of steel balls + porcelain balls is 55%, the yield of grinding products -0.075mm is less than 85%, and when the filling rates are 60% and 65%, the experimental requirements are met.
[0062] However, when the filling rate of the grinding medium is too high (above 65%), the yield of -0.075mm is not greatly improved, the yield of -0.045+0.038mm is even lower, and the yield of -0.030mm is even higher, resulting in over-grinding.
[0063] Considering the grinding effect and grinding energy consumption factors comprehensively, a filling rate of 60% was selected as the optimal filling rate for the tower mill grinding experiment.
[0064] like Figure 3 As shown in the figure, compared with the indicators obtained after magnetic separation of the products after steel ball and all-ceramic ball grinding, the grade of magnetic concentrate obtained after magnetic separation of the products after magnetic separation of all-ceramic ball and steel ball + ceramic ball grinding is greater than that of magnetic concentrate obtained after magnetic separation of the products after steel ball grinding; the grade of tailings after magnetic separation of the products after all-ceramic ball grinding is reduced from 5.62% to 4.75%, and the grade of tailings after magnetic separation of the products after steel ball + ceramic ball grinding is reduced from 5.62% to 5.04%; in terms of recovery rate, the recovery rate of magnetic concentrate obtained after magnetic separation of the products after magnetic separation of all-ceramic ball grinding is 98.79%, while the recovery rate of concentrate after steel ball grinding is 97.95%, and the recovery rate of concentrate after mixed grinding of steel ball + ceramic ball is 98.76%.
[0065] Based on the experimental results and the production needs of the beneficiation plant, the recommended porcelain ball scheme is: Φ25mm:Φ20mm:Φ15mm=60%:20%:20%.
[0066] The tower mill model is TGTM-1000, and the effective volume of the cylinder is 49m 3 It is recommended that the initial filling rate be set at 60%, the designed porcelain ball filling rate at 56%, and the steel ball filling rate at 4%. The calculation of the porcelain ball and steel ball filling amount is: The specific gravity of the porcelain ball pile is 2.2t / m 3 According to the estimation, the total amount of porcelain balls initially installed is 49m 3 ×56%×2.2t / m 3 ≈60t; among which, the initial Φ25mm is 36t, Φ20mm is 12t, and Φ15mm is 12t; the specific gravity of the steel ball is 4.85t / m 3 According to the estimation, the total amount of steel balls initially loaded is 49m 3 ×4%×4.85t / m 3 ≈10t. When loading the balls for the first time, all ceramic balls are loaded, 7 tons of steel balls are loaded, and 3 tons are reserved for additional loading according to production conditions. Φ25mm ceramic balls and Φ20mm steel balls can be added on a daily basis.
[0067] Working principle: The present invention introduces nano-composite ceramic balls as grinding media. Compared with traditional steel balls, nano-composite ceramic balls have lower crushing energy requirements and can significantly reduce the generation of over-abrasive particles (-0.019mm). At the same time, due to its high filling rate and larger specific surface area, it enhances the grinding ability of fine-grained minerals and improves the grinding efficiency. In specific applications, firstly, the material fed into the tower mill is screened, the feed particle size composition is analyzed, and the appropriate grinding medium size is selected. Through a series of experiments, the optimal ceramic ball diameter ratio is determined to be Φ25mm:Φ20mm:Φ15mm=60%:20%:20%, and on this basis, Φ25mm steel balls with a volume ratio of 4% are added. Under this ratio scheme, the -0.075mm yield and qualified particle yield in the grinding product are increased, and the under-abrasive particle yield is reduced, achieving the goal of increasing the -325+400 mesh particle yield.
[0068] In addition, the process can obtain the best particle size distribution at a grinding concentration of 67%. When the total filling rate is 60%, it can not only ensure a good grinding effect, but also avoid the problem of over-grinding caused by too high a filling rate. The whole process not only improves the concentrate grade and recovery rate, but also achieves the purpose of energy saving and consumption reduction, reducing production costs.
[0069] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0070] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and variations can be made to the embodiments without departing from the principles and spirit of the invention.
Claims
1. A low-carbon grinding process for improving the yield of -325+400 mesh size, characterized in that: include: S1. Perform a screening experiment on the material fed into the tower mill to obtain a feed particle size composition table; S2. Combined with the feed particle size composition table, two diameters of steel balls were selected for benchmark experiments, with a ratio of 1:1, a filling rate of 40%, and a grinding concentration of 65%, to obtain the optimal grinding time; S3. To explore the effect of different diameters of ceramic balls on the particle size distribution of grinding products, grinding was carried out under the conditions of filling rate of 60% and grinding concentration of 65% with single ceramic ball sizes of Φ15mm, Φ20mm, Φ25mm and Φ30mm respectively; S4, combining the single porcelain ball size experimental results in S3, conducting experiments on various porcelain ball diameter ratio conditions to determine an optimal porcelain ball diameter ratio scheme; S5. Determine the initial ball loading system of the porcelain balls, determine the optimum filling rate of the porcelain balls, and on this basis select different concentrations to conduct grinding concentration tests to obtain the optimum grinding concentration; S6. Add steel balls appropriately to the determined ceramic ball ratio to reduce the under-abrasive grade, and select the most suitable size of steel balls as the steel ball + ceramic ball mixed grinding medium by repeating the operation of S3; S7. Determine the steel ball + ceramic ball mixed grinding scheme, select several steel ball volume ratio schemes, and compare the experimental results with all-ceramic ball grinding. By adding steel balls to the optimal ceramic ball ratio, the -0.075mm yield and qualified particle size yield in the grinding product are increased, and the under-grinding particle size yield is reduced. S8. Determine the conditions for the mixed grinding of steel balls and porcelain balls in the tower mill, grind at total filling rates of 55%, 60%, and 65%, select the best filling rate for the tower mill grinding experiment, and determine the final grinding plan.
2. A low-carbon grinding process for improving the yield of -325+400 mesh size according to claim 1, characterized in that: In response to S2, steel balls with diameters of Φ20 mm and Φ15 mm were selected as benchmark experiments, and the optimal grinding time was determined to be 5 minutes.
3. A low-carbon grinding process for improving the yield of -325+400 mesh size according to claim 2, characterized in that: According to S4, Φ20mm porcelain ball is selected as the optimal size, and the best porcelain ball diameter ratio is determined to be Φ25mm:Φ20mm:Φ15mm=60%:20%:20%.
4. A low-carbon grinding process for improving the yield of -325+400 mesh size according to claim 3, characterized in that: As described in S5, during the filling rate experiment, as the filling rate of the porcelain balls increased, the yield of -0.075mm in the grinding product gradually increased. When the filling rate reached 60%, the yield of -0.075mm was 78.51%, the yield of the under-abrasive grade (+0.15mm) was 9.03%, and the yield of -0.045+0.038mm was 24.77%, and the grinding effect was optimal.
5. A low-carbon grinding process for improving the yield of -325+400 mesh size according to claim 4, characterized in that: As mentioned in S6, when 25 mm steel balls are used as grinding media, the yield of the new-0.075 mm diameter steel balls is higher than that of other diameter steel balls, and the yield of the under-abrasive grade is the lowest.
6. A low-carbon grinding process for improving the yield of -325+400 mesh size according to claim 5, characterized in that: As described in S7, after adding steel balls, the -0.075mm yield and qualified particle size yield in the grinding product increased, and the under-abrasive particle size yield decreased. Among them, when the volume of steel balls accounted for 4%, the -0.075mm yield of the grinding product was the highest, which was 87.33%, and the under-abrasive particle size content was the lowest, which was 6.95%.
7. A low-carbon grinding process for improving the yield of -325+400 mesh size according to claim 6, characterized in that: The process is applicable to the tower mill model TGTM-1000, with an effective cylinder volume of 49m 3 Among them, the total amount of initially installed porcelain balls is about 60 tons, the total amount of initially installed steel balls is about 7 tons, and 3 tons of steel balls are reserved for additional additions depending on production conditions. Φ25mm porcelain balls and Φ20mm steel balls are added on a daily basis.
Citation Information
Patent Citations
Ore grinding method adopting ceramic dielectric applied to tower mill
CN105855000A
Ore grinding method using ceramic ball as coarse grinding medium
CN114453086A
Method and system for selecting specification of ball mill with ceramic ball as ore grinding medium
CN115245861A
Steel section and ceramic ball mixed grinding method in horizontal ball mill for minerals easy to overgrind
CN116651575A
Design method of porcelain ball grinding ball mill and porcelain ball grinding ball mill thereof
CN118768042A